URGENSI PERENCANAAN SDM SEBAGAI UPAYA PENYELARASAN STRATEGI BISNIS PERUSAHAAN: KAJIAN LITERATUR - Arifin, Antoni Ludfi (Program Studi Manajemen Fakultas Ekonomi Universitas Siliwangi, 2021)
HR planning is a strategic matter in implementing corporate strategy, through HR planning it can increase the company's chances of getting the right people, in the right place, at the time needed. Good HR planning must be in-line with the company's vision, mission, long-term objectives, and short-term objectives. This HR planning must be able to be implemented properly by the HR division in order to find the best candidate for the company. This research is a descriptive qualitative research by analyzing the relevant literature related to HR planning. The results showed that the company must be able to compile HR planning that is in line with its vision, mission, long-term objectives, and short-term objectives; the HR division must be able to translate HR planning based on organizational design, job design, in the form of job descriptions, tasks, responsibilities, authorities, as the basis for determining HR planning; HR planning tailored to the company's business development; workload analysis, become the basis for HR planning; and employee turnover rate, can be used as a determination of the company's HR planning.